Use of expanded‐criteria donors and > 85 KDPI kidneys for pediatric kidney transplantation in the United States - Kizilbash, Sarah J.; Evans, Michael D.; Chinnakotla, Srinath; Chavers, Blanche M. (American journal of transplantation, 2021)
Pediatric kidney transplant outcomes associated with expanded‐criteria donors (ECD) and high Kidney Donor Profile Index (KDPI) kidneys are unknown. We reviewed the Scientific Registry of Transplant Recipients data from 1987‐2017 to identify 96 ECD and 92 > 85 KDPI kidney recipients (<18 years). Using propensity scores, we created comparison groups of 375 non‐ECD and 357 ≤ 85 KDPI recipients for comparisons with ECD and > 85 KDPI transplants, respectively. We used Cox regression for patient/graft survival and sequential Cox approach for survival benefit of ECD and > 85 KDPI transplantationvs remaining on the waitlist. After adjustment, ECD recipients were at significantly increased risk of graft failure (adjusted hazard ratio [aHR] = 1.6; P = .001) but not of mortality (aHR = 1.33; P = .15) compared with non‐ECD recipients. We observed no survival benefit of ECD transplants vs remaining on the waitlist (aHR = 1.05; P = .83). We found no significant difference in graft failure (aHR = 1.27; P = .12) and mortality (aHR = 1.41; P = .13) risks between > 85 KDPI and ≤ 85 KDPI recipients. However, > 85 KDPI transplants were associated with a survival benefit vs remaining on the waitlist (aHR = 0.41; P = .01). ECD transplantation in children is associated with a high graft loss risk and no survival benefit, whereas > 85 KDPI transplantation is associated with a survival benefit for children vs remaining on the waitlist. For pediatric candidates, compared to waiting for a better quality kidney, transplants using > 85 KDPI kidneys are associated with a survival benefit while expanded criteria donor kidneys are not.